Implementation of the Program Keluarga Harapan (PKH) in Reducing Poverty and Preventing School Dropouts in Regions Great Aceh - Rahmi, (Jurnal Serambi Ilmu, 2024)
In the many country the poor are still the main problem in the development. In the context of poverty alleviation, the government issued a program for households, namely the Program Keluarga Harapan (PKH). This study aims to find out how the mechanism of PKH implementation in reducing poverty in Seulimum District, Aceh Besar District and to find out how the influence of PKH in preventing dropouts in the community of Seulimum District, Aceh Besar District. The method used in this study is a qualitative descriptive method. Based on the results of research that has been carried out, it shows that the implementation of the Family Hope Program (PKH) has been going very well. This can be seen from every implementation process that runs smoothly. When viewed from the condition of the recipients of PKH assistance, they use it to overcome economic problems and help children who are out of school, health and nutrition costs for pregnant women, postpartum mothers, and children under 6 years.